Influence of Deposition Parameters on the Surface Morphology and Photocatalytic Properties of WO3 Thin Films Synthesized by Magnetron Sputtering at a Glancing Angle Deposition - Abduvalov, A.; Taubaldiyeva, Zh.; Baigarin, K. (Recent Contributions to Physics, 2025)
The growing need for sustainable energy has intensified research on photoelectrochemical (PEC) water splitting for hydrogen production. Tungsten trioxide (WO3) is a promising photoanode due to its stability, suitable bandgap ( 2.4–2.8 eV), and strong visible-light absorption. However, performance limitations arise from short hole diffusion length and high recombination rates. This study examines the effect of substrate rotation during magnetron sputtering on WO3 thin films’ morphology and PEC performance, employing the glancing angle deposition technique to achieve nanostructured films that enhance light trapping. SEM analysis reveals that films deposited without rotation exhibit greater porosity, improving light absorption and charge transport. As a result, these films demonstrate higher photocurrent density and enhanced electrochemical impedance properties. These findings highlight the significance of deposition dynamics in optimizing WO3 for PEC applications. This study provides insights into controlling thin film morphology to improve PEC efficiency, contributing to the development of more effective water-splitting devices.